INVESTIGATION OF STARTING BEHAVIOUR OF A FREE PISTON LINEAR GENERATOR ENGINE - ZAINAL ABIDIN, EZRANN ZHARIF (2013)
The current global crisis is now wrapped around the transportation industry whereby emissions and fuel prices are increasing. It is clear that the transportation system have polluted globally with CO, NOx and soot. Due to the reasons mentioned, environmental policymakers have created laws that limit the emission level produced by the internal combustion engine. As a result, it pushes researchers to develop new methods and technologies to tackle this problem and to come up with a highly efficient internal combustion engine with lower emissions. A two-stroke free piston linear-generator engine (FPLG) as prime mover for electric power generation has been developed to address these issues. A linear engine coupled to a permanentmagnet assembly becomes a linear-generator (LG) which can produce electrical power. Its working principle is based on the free-piston two-stroke engine with direct injection.